Strategi Optimalisasi Pengelolaan Wakaf Tanah: Analisis Bibliometrik - Muhamad Arul Rizky; Indra (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the optimization strategy of land waqf management using a bibliometric approach conducted using biblioshiny, an R-based application. Descriptive statistical methods were used, Data were analyzed from 189 research publications in scopus with the keyword "Land Waqf". This study shows that most of the most productive authors are from Malaysia, the most popular keywords with the topic of land waqf are "Islamism" and "historical geography". The research findings are expected to provide innovative solutions in improving the productivity and transparency of land waqf management. This study offers a novel contribution by combining a comprehensive literature review and the application of data analysis technology in the context of waqf management in Indonesia